Potensi Asap Cair Kulit Kopi Robusta Dalam Menghambat Pertumbuhan Curvularia sp. di Pre-Nursery Kelapa Sawit - Yusmar Mahmud; Sinar Roma Rezky Pulungan; Bakhendri Solfan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Oil palms are susceptible to the pre-nursery stage of plant mortality caused by the Curvularia sp. pathogen, affecting various crops. Attacks by Curvularia sp. not only make oil palm production less efficient, but they are also notoriously difficult to manage. As a botanical fungicide, liquid smoke from strong coffee husks is an alternate control strategy. This research seeks to assess the efficacy of liquid smoke from robusta coffee husks in preventing the development of Curvularia sp. in oil palm seedlings. From January through April 2024, the laboratory work at UIN Agriculture Research Development Science Agrotechnology, Faculty of Agriculture and AnimalHHusbadry, State Islamic University Sultan Syarif Kasim Riau, focused on pathology, entomology, microbiology, soil and land science, and other related topics. This research used a fully randomized design (CRD) experimental approach with six treatments: a control group that did not get any liquid smoke and did not have a fungal infection, and five groups that received varying concentrations of liquid smoke with pathogen infection:0%, 1%, 2%, 3%, and 4%. Research has shown that at a concentration of 4%, robust coffee husk liquid smoke—which contains 4.24% total phenol and a pH of 4.61—could effectively or partially suppress the development of Curvularia sp. on oil palm seedlings. When comparing treatments, there were statistically significant changes in the number of infected leaves, the number of spots on the leaves, and the area of the spots, but no changes in the total number of leaves.